Corporate R&D and the performance of food-processing firms: Evidence from Europe, Japan and North America - Heinrich Hockmann; Pedro Andres Garzon Delvaux; Peter Voigt; Pavel Ciaian; Sergio Gomez y Paloma (Bio-based and Applied Economics, 2018)
This paper investigates the impact of corporate research and development (R&D) on firm performance in the food-processing industry. We apply Data Envelopment Analysis (DEA) with two step bootstrapping using a corporate data for 307 food-processing firms from the EU, US, Canada and Japan for the period 1991-2009. The estimates suggest that R&D has a positive effect on the firms' performance, with marginal gains decreasing in the R&D level as well as the performance differences are detected across regions and food sectors. R&D investments in food processing can deliver productivity gains, beyond the high-tech sectors generally favoured by innovation policy.
Keywords: O30; L66; 330; Corporate R&D; DEA; double bootstrapping; food-processing industry